HIV sexual risk behavior among low-income women experiencing intimate partner violence: the role of posttraumatic stress disorder. - Cavanaugh, Courtenay E; Hansen, Nathan B; Sullivan, Tami P (AIDS and behavior, 2010)
Posttraumatic stress disorder resulting from intimate partner violence (IPV-related PTSD), drug problems, and alcohol problems were tested as correlates of women's sexual risk behavior. Participants were 136 low-income women experiencing physical violence by a male partner during the past 6 months. Sexual risk behavior was assessed by whether women had unprotected sex with a risky primary partner (i.e., HIV-positive, injection drug user, and/or nonmonogamous), unprotected sex with a risky nonprimary partner (i.e. HIV-positive or unknown status), or traded sex during the past 6 months. Nearly one in five women engaged in these recent sexual risk behaviors. Simultaneous logistic regression results revealed IPV-related PTSD, but not drug or alcohol problems, was significantly associated with sexual risk behavior while controlling for childhood abuse and demographic covariates. Women with IPV-related PTSD had four times greater odds of recent sexual risk behavior compared to women without IPV-related PTSD. Implications for HIV prevention interventions are discussed.
Keywords: Adolescent; Adult; Domestic Violence; Female; HIV Infections; Humans; Logistic Models; Male; Middle Aged; Poverty; Risk-Taking; Sexual Behavior; Sexual Partners; Stress Disorders, Post-Traumatic; Young Adult